Mind the Gap: A Theory Development Approach for Explaining the Divergence of Human Information Processing Capacity and Information Amount - Bruckner, Moritz; Grüning, Maximilian; Lindenmayr, Michaela; Schmalenbach, Kian (2022)
While the amount of available information increases, humans have limited capacity to store and process such information amounts. We know where and when such limits are exhausted, but we know little about the diverging gap between limited human information processing capacity and unlimited information supply. Based on the thought-gear model of theorizing, we conceptualize a theoretical model to describe implications and effects of this diverging gap. With our research, we describe the increasing reliance on information technology that makes overwhelming information amounts processable for the human brain, and we provide insights on consequences of this increasing dependency. In addition, we contribute to the body of literature by providing a macro-level model to support an explanation of this phenomenon. Furthermore, our results shed light on three strategies to meet this gap, responding to calls for research on human-technology interaction and for the digitization of the individual.
Keywords: Artificial Intelligence; Recommender Systems; Information Overload